Answer:
The rule for the linear function will be:
![f(x) = -2x+5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-2x%2B5)
Step-by-step explanation:
We know that linear function can be represented using the slope-intercept formula
y = mx+b
where m is the slope and b is the y-intercept
Given the function is linear
Taking two points from the table to determine the slope
![\mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![\left(x_1,\:y_1\right)=\left(1,\:3\right),\:\left(x_2,\:y_2\right)=\left(2,\:1\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%281%2C%5C%3A3%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%282%2C%5C%3A1%5Cright%29)
![m=\frac{1-3}{2-1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B1-3%7D%7B2-1%7D)
![m=-2](https://tex.z-dn.net/?f=m%3D-2)
Using the point-slope form of the line equation
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
where m is the slope of the line and (x₁, y₁) is the point
substituting the values m = -2 and the point (1, 3)
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
![y - 3 = -2 (x-1)](https://tex.z-dn.net/?f=y%20-%203%20%3D%20-2%20%28x-1%29)
![y-3 = -2x+2](https://tex.z-dn.net/?f=y-3%20%3D%20-2x%2B2)
adding 3 to both sides
![y-3+3 = -2x+2+3](https://tex.z-dn.net/?f=y-3%2B3%20%3D%20-2x%2B2%2B3)
![y = -2x+5](https://tex.z-dn.net/?f=y%20%3D%20-2x%2B5)
or
![f(x) = -2x+5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-2x%2B5)
Therefore, the rule for the linear function will be:
![f(x) = -2x+5](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-2x%2B5)